The equation of the perpendicular bisector of line segment joining points A (4, 5) and B (−2, 3) is
(a) 2x – y + 7 = 0 (b) 3x + 2 y – 7 = 0
(c) 3x – y – 7 =0 (d) 3x + y – 7 = 0
Get live Maths 1-on-1 Classs - Class 6 to 12
CBSE Class 10 Sample Paper for 2022 Boards - Maths Standard [MCQ]
Question 2
Question 3
Question 4 Important
Question 5 Important
Question 6
Question 7
Question 8 Important
Question 9 Important
Question 10
Question 11 Important
Question 12
Question 13 Important
Question 14
Question 15 Important
Question 16
Question 17 Important
Question 18
Question 19 Important
Question 20
Question 21 Important
Question 22 Important
Question 23 Important
Question 24
Question 25 Important
Question 26
Question 27
Question 28 Important
Question 29 Important
Question 30
Question 31 Important You are here
Question 32 Important
Question 33
Question 34 Important
Question 35
Question 36 Important
Question 37 Important
Question 38
Question 39 Important
Question 40
Question 41 (Case Based Question) Important
Question 42 (Case Based Question)
Question 43 (Case Based Question) Important
Question 44 (Case Based Question)
Question 45 (Case Based Question)
Question 46 (Case Based Question)
Question 47 (Case Based Question) Important
Question 48 (Case Based Question)
Question 49 (Case Based Question) Important
Question 50 (Case Based Question) Important
CBSE Class 10 Sample Paper for 2022 Boards - Maths Standard [MCQ]
Last updated at March 22, 2023 by Teachoo
Get live Maths 1-on-1 Classs - Class 6 to 12
Question 31 The equation of the perpendicular bisector of line segment joining points A (4, 5) and B (−2, 3) is (a) 2x – y + 7 = 0 (b) 3x + 2 y – 7 = 0 (c) 3x – y – 7 =0 (d) 3x + y – 7 = 0 Let Line l be the perpendicular bisector of AB And let it intersect AB at point P Let point P be any point on Line l By symmetry AP = BP √(( 𝑥 −4 )2+(𝑦−5)2) = √(( 𝑥 −(−2))2+(𝑦−3)2) √(( 𝑥 −4 )2+(𝑦−5)2) = √(( 𝑥+2)2+(𝑦−3)2) Squaring both sides ( 𝒙 −𝟒)𝟐+(𝒚−𝟓)𝟐 = ( 𝒙+𝟐)𝟐+(𝒚−𝟑)𝟐 𝑥^2+16−8𝑥+𝑦^2+25−10𝑦=𝑥^2+4+4𝑥+𝑦^2+9−6𝑦 16−8𝑥+25−10𝑦=4+4𝑥+9−6𝑦 −8𝑥−10𝑦+41=4𝑥−6𝑦+13 0 =4𝑥−6𝑦+13+8𝑥+10𝑦−41 0 =4𝑥+8𝑥−6𝑦+10𝑦+13−41 0 =12𝑥+4𝑦−28 12𝑥+4𝑦−28=0 Dividing by 4 both sudes 𝟑𝒙+𝒚−𝟕=𝟎 So, the correct answer is (d)